Electrolyte and lithium ion battery
By using fluoromononitrile compounds and fluorovinyl carbonate electrolyte in lithium-ion batteries, combining the proportion adjustment of linear ester and cyclic ester solvent, the poor interfacial stability and high temperature performance of traditional electrolytes under high conductivity are solved. The poor problem has significantly improved the low-temperature fast charging and high-temperature cycling performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202411326842.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
AI Technical Summary
Traditional high-conductivity electrolytes have poor interface stability and poor high-temperature performance under high conductivity, which limits the cycle life and high-temperature applications of lithium-ion batteries.
Using an electrolyte containing fluoromononitrile compounds and fluorovinyl carbonate, the low-temperature kinetic properties and high-temperature interface stability of the electrolyte are improved by adjusting the ratio of linear ester solvents and cyclic ester solvents, forming an efficient interface film formation , jointly improve the low-temperature fast charging and high-temperature cycling performance of lithium-ion batteries.
The low-temperature fast charging performance, low-temperature discharge performance and high-temperature circulation performance of lithium-ion batteries have been improved, reducing the side reactions of high-temperature interfaces and low-temperature lithium-ion phenomena, ensuring the stability and life of the battery at high and low temperatures.
Smart Images

Figure BDA0005055639200000151 
Figure BDA0005055639200000161 
Figure BDA0005055639200000171
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to an electrolyte and a lithium ion battery comprising the electrolyte. Background Art
[0002] High conductivity electrolytes can reduce the internal resistance of batteries and increase the charging and discharging speed of batteries, thereby meeting the needs of fast charging and high energy density. However, traditional high conductivity electrolytes are often accompanied by poor interface stability and poor high temperature performance under high conductivity. Poor interface stability may cause side reactions between the electrolyte and the positive and negative electrode materials during the charging and discharging process of the battery, affecting the cycle life of the battery; while poor high temperature performance limits the application of the battery in high temperature environments. Therefore, in order to take into account both interface stability and high temperature stability, it is particularly important to develop new high conductivity electrolytes. Summary of the invention
[0003] The invention provides an electrolyte and a lithium ion battery comprising the electrolyte. The electrolyte has high conductivity and can take into account both interface stability and high temperature stability under high conductivity.
[0004] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0005] The first aspect of the present invention provides an electrolyte, comprising an additive A, an additive B, a linear ester solvent and a cyclic ester solvent; the additive A comprises a fluoromononitrile compound, and the additive B comprises fluoroethylene carbonate; based on the total mass of the electrolyte, the mass content of the additive A is a wt%, and the mass content of the additive B is b wt%; the electrolyte satisfies the relationship: b≥a / 5; based on the total mass of the electrolyte, the mass content of the linear ester solvent is ≥30wt%, and the mass content of the ethylene carbonate contained in the cyclic ester solvent is ≤10wt%.
[0006] A second aspect of the present invention provides a lithium ion battery, the lithium ion battery comprising the electrolyte of the first aspect of the present invention, a positive electrode and a negative electrode;
[0007] The positive electrode comprises lithium cobalt oxide;
[0008] Based on the total mass of the electrolyte, the mass content of cobalt element in the electrolyte is e ppm;
[0009] The mass content a wt % of the additive A and the mass content e ppm of the cobalt element in the electrolyte satisfy the relationship: a≥e / 500.
[0010] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:
[0011] The fluoromononitrile compounds included in the electrolyte of the present invention have a high dielectric constant and a low viscosity, which can improve the low-temperature kinetic properties of the electrolyte and make it have a high low-temperature conductivity. At the same time, the addition of fluoroethylene carbonate (FEC) can further enhance the interfacial film formation and improve its interfacial stability and thermal stability at high temperatures. The two additives work together to improve the low-temperature fast charging performance and high-temperature interface stability of the lithium-ion battery, reduce the consumption of the electrolyte by high-temperature interface side reactions and low-temperature lithium precipitation, thereby achieving better low-temperature fast charging performance, low-temperature discharge performance and high-temperature cycle performance.
[0012] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. DETAILED DESCRIPTION
[0013] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0014] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0015] The first aspect of the present invention provides an electrolyte, comprising an additive A, an additive B, a linear ester solvent and a cyclic ester solvent; the additive A comprises a fluoromononitrile compound, and the additive B comprises fluoroethylene carbonate;
[0016] Based on the total mass of the electrolyte, the mass content of the additive A is awt%, the mass content of the additive B is b wt%, and the electrolyte satisfies the relationship: b≥a / 5;
[0017] Based on the total mass of the electrolyte, the mass content of the linear ester solvent is ≥30wt%, and the mass content of ethylene carbonate (EC) in the cyclic ester solvent is ≤10wt%.
[0018] The fluoromononitrile compound included in the electrolyte of the present invention has a high dielectric constant and a low viscosity, which can improve the low-temperature kinetics of the electrolyte and make it have a high low-temperature conductivity. At the same time, the addition of fluoroethylene carbonate (FEC) can further enhance the interfacial film formation and improve its interfacial stability and thermal stability at high temperatures. The two additives work together to improve the low-temperature fast charging performance and high-temperature interface stability of the lithium-ion battery, reduce the consumption of the electrolyte by high-temperature interface side reactions and low-temperature lithium precipitation, thereby achieving better low-temperature fast charging performance, low-temperature discharge performance and high-temperature cycle performance.
[0019] Specifically, the additive A fluorocarbon mononitrile compound used in the present invention has good low-temperature kinetics, and the low-temperature conductivity of the relevant electrolyte is high, which can make lithium ions in the electrolyte shuttle quickly and realize low-temperature fast charging; and fluoroacetonitrile has high oxidation resistance, and it is easy to form a film when reduced to the negative electrode, so the interface side reaction itself is relatively low, but the side reaction is aggravated at high temperature; and the additive B fluoroethylene carbonate (FEC) can form a high-temperature stable and elastic SEI film at the negative electrode interface, and the film has excellent protection ability, which can inhibit the side reaction of fluorocarbon mononitrile at the interface at higher temperatures; thereby, the fluorocarbon mononitrile compound and fluoroethylene carbonate (FEC) synergistically improve the low-temperature fast charging and high-temperature interface of the battery, and reduce the high-temperature interface side reaction and low-temperature lithium precipitation phenomenon;
[0020] In addition, the present invention further adjusts the contents of different solvents in the electrolyte system so that the mass content of ethylene carbonate EC in the cyclic ester solvent is ≤10wt%, and the mass content of the linear ester solvent is ≥30wt%. It can balance the rate performance and high temperature performance of the battery while ensuring the low temperature performance, because the appropriate addition of the cyclic ester EC solvent can effectively improve the conductivity and cycle stability of the electrolyte, and the presence of the linear ester solvent (for example: DEC and EMC) can maintain good fluidity of the electrolyte at low temperatures; and through reasonable use, the two can exert a significant synergistic effect, significantly optimizing the overall high and low temperature rate performance and cycle stability of the lithium ion battery.
[0021] In a specific embodiment, the mass content of the linear ester solvent is ≥30wt%. Exemplarily, the mass content of the linear ester solvent can be 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt%. Due to the low melting point and viscosity of linear ester solvents, they can effectively reduce the overall viscosity of the electrolyte and improve the conductivity and cycle stability of the electrolyte at low temperatures. Therefore, the mass content of the linear ester solvent in the electrolyte system should not be too small, otherwise it will affect the conductivity of the electrolyte and the quality of the SEI film.
[0022] In a specific embodiment, the mass content of ethylene carbonate in the cyclic ester solvent is ≤10wt%. Exemplarily, the mass content of the cyclic ester solvent can be 10wt%, 9wt%, 8wt%, 7wt%, 6wt%, 5wt%, 4wt%, 3wt%, 2wt%, 1wt%, 0wt%. Due to its high dielectric constant and good film-forming ability, the cyclic ester solvent can also improve the performance of the battery at high temperature, maintain high conductivity and stability, and is conducive to improving the high-temperature cycle performance of the battery. However, the content of ethylene carbonate in the cyclic ester solvent should not exceed 10%, because the cyclic ester solvent ethylene carbonate has a high dielectric constant. When the content of these solvents is too high, the dielectric constant of the entire electrolyte will increase, but this is not conducive to the dissociation of lithium salts, thereby reducing the conductivity of the electrolyte and affecting the low-temperature conductivity of the battery.
[0023] According to the electrolyte of the present invention, based on the total mass of the electrolyte, the mass content of the additive A is a wt%, wherein 2wt%≤a wt%≤50wt%, exemplary, a wt% can be 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%. If the content of fluoromononitrile compounds is too low, the improvement of the low-temperature conductivity of the battery will not be obvious. If the content of fluoromononitrile compounds is too high, the cycle stability of the battery will be affected due to its damage to the negative electrode interface. Therefore, the present invention can further avoid the deterioration of its low-temperature performance by controlling the mass content of fluoromononitrile compounds within a suitable range, taking into account the low-temperature fast charging performance and cycle stability performance of the battery. In a preferred embodiment, 3wt%≤awt%≤15wt%.
[0024] According to the electrolyte of the present invention, based on the total mass of the electrolyte, the mass content of the additive B is bwt%, wherein 1wt%≤bwt%≤20wt%, and exemplary, bwt% may be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 15wt%, 20wt%. Wherein, when the content of the additive B fluoroethylene carbonate is insufficient, a complete SEI film cannot be formed on the surface of the negative electrode, which will cause the electrolyte to continuously decompose and the electrode material to degrade, and reduce the cycle stability and life of the battery; when the content of fluoroethylene carbonate is too high, excessive FEC may cause the FEC to decompose more HF at high temperature, resulting in a significant deterioration of the high temperature performance of the battery. Therefore, the content of the additive B can be further controlled to avoid the influence on the cycle life and high temperature stability of the battery. In a preferred embodiment, 5wt%≤bwt%≤15wt%.
[0025] According to the electrolyte of the present invention, the fluoromononitrile compound includes at least one of fluoropropionitrile, 3,3-difluoropropionitrile, 2-fluoroisobutyronitrile, fluoroacetonitrile and derivatives thereof.
[0026] According to the electrolyte of the present invention, the linear ester solvent includes at least one of propyl propionate (PP), ethyl propionate (EP), ethyl butyrate (EB), diethyl carbonate (DEC), ethyl methyl carbonate (EMC) and derivatives thereof.
[0027] According to the electrolyte of the present invention, the cyclic ester solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC) and vinylene carbonate (VC).
[0028] According to the electrolyte of the present invention, the electrolyte further comprises a lithium salt, a sulfur-containing additive, a boron-containing additive and a nitrile compound.
[0029] In a specific embodiment, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), and lithium bis(trifluoromethylsulfonyl)imide (LiFSI). In a specific embodiment, based on the total mass of the electrolyte, the mass content of the lithium salt is 8wt% to 30wt%. Exemplarily, the mass content of the lithium salt can be 8wt%, 10wt%, 12wt%, 14wt%, 16wt%, 18wt%, 20wt%, 22wt%, 24wt%, 26wt%, 28wt%, 30wt%.
[0030] In a specific embodiment, the sulfur-containing additive includes at least one of 1,3-propane sultone (PS), 1-propylene-1,3-sultone, 5-methylthiothiophene 2,2-dioxide, 1,3-propylene sultone, 2,4-butane sultone and 1,4-butane sultone. In a specific embodiment, based on the total mass of the electrolyte, the mass content of the sulfur-containing additive is 0.5wt% to 5wt%. Exemplarily, the mass content of the sulfur-containing additive can be 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%.
[0031] In a specific embodiment, the boron-containing additive includes at least one of lithium tetrafluoroborate, lithium difluorooxalate borate (LiDFOB), and lithium dioxalate borate. In a specific embodiment, based on the total mass of the electrolyte, the mass content of the boron-containing additive is 0.1wt% to 4wt%. Exemplarily, the mass content of the boron-containing additive can be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 2wt%, 3wt%, 4wt%.
[0032] In a specific embodiment, the nitrile compound includes one or more of 1,3,5-hexanetrinitrile (HTCN), adiponitrile (ADN), succinonitrile, ethylene glycol bis(propionitrile) ether and tris(3-cyanopropyl) phosphate. In a specific embodiment, based on the total mass of the electrolyte, the mass content of the nitrile compound is 1wt% to 6wt%. Exemplarily, the mass content of the nitrile compound can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%.
[0033] According to the electrolyte of the present invention, based on the total mass of the electrolyte, when the lithium salt includes lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and / or lithium bis(fluorosulfonyl)imide (LiFSI), the mass content of the lithium salt is d wt%; the electrolyte also satisfies the relationship: d≤2a. A certain amount of LiTFSI and LiFSI can improve the kinetics of the electrolyte, but too high a content d of LiTFSI and LiFSI will significantly increase the viscosity of the electrolyte and deteriorate the kinetics of the electrolyte; in addition, the higher the content of additive A, the higher the mass content of lithium salt d can be dissolved in the electrolyte, so when the content of additive A is higher, the content of lithium salt d can also be higher, but it cannot exceed a specific range, that is, it must satisfy the relationship d≤2a, thereby further avoiding the deterioration of the kinetic performance of the electrolyte. In a specific embodiment, 0wt%≤d wt%≤20wt%. Exemplarily, the value of d wt % can be 0 wt %, 1 wt %, 2 wt %, 3 wt %, 4 wt %, 5 wt %, 6 wt %, 7 wt %, 8 wt %, 9 wt %, 10 wt %, 15 wt %, or 20 wt %.
[0034] The second aspect of the present invention provides a lithium ion battery, which includes the electrolyte, positive electrode and negative electrode of the first aspect of the present invention; the positive electrode contains lithium cobalt oxide; based on the total mass of the electrolyte, the mass concentration of cobalt element in the electrolyte is eppm; the mass content a wt% of the additive A and the mass concentration e ppm of the cobalt element in the electrolyte satisfy the relationship: a≥e / 500.
[0035] It should be noted that the cobalt element in the electrolyte comes from the positive electrode active material lithium cobalt oxide, and its mass concentration in the electrolyte is e ppm, which is used to represent the proportion of the cobalt element in the total electrolyte solution system and can be measured by the ICP test method. When the content of the additive A fluoromononitrile compound is too little, it will lead to insufficient protection of the positive electrode active material lithium cobalt oxide, which is easy to cause the decomposition reaction of the positive electrode active material under high voltage to intensify, thereby reducing the cycle stability and life of the battery. Therefore, in order to avoid the intensification of the decomposition reaction of the positive electrode active material under high voltage, it is necessary to control the content of additive A, but excessive content of additive A will also have adverse effects. Please refer to the above description of the content of additive A. Therefore, the present invention further measures the content of cobalt in the electrolyte and adjusts the relationship between a and e to satisfy a≥e / 500, which can further avoid affecting the cycle stability and life of the battery. In a specific embodiment, e≤10000ppm.
[0036] According to the battery of the present invention, the surface capacity of the negative electrode is 2 mAh / cm 2 -5mAh / cm 2For example, the surface capacity of the negative electrode can be 2 mAh / cm 2 、2.1mAh / cm 2 、2.2mAh / cm 2 、2.3mAh / cm 2 、2.4mAh / cm 2 、2.5mAh / cm 2 、2.6mAh / cm 2 、2.7mAh / cm 2 、2.8mAh / cm 2 、2.9mAh / cm 2 、3mAh / cm 2 、3.1mAh / cm 2 、3.2mAh / cm 2 、3.3mAh / cm 2 、3.4mAh / cm 2 、3.5mAh / cm 2 、3.6mAh / cm 2 、3.7mAh / cm 2 、3.8mAh / cm 2 、3.9mAh / cm 2 , 4mAh / cm 2 、4.1mAh / cm 2 、4.2mAh / cm 2 、4.3mAh / cm 2 、4.4mAh / cm 2 、4.5mAh / cm 2 、4.6mAh / cm 2 、4.7mAh / cm 2 、4.8mAh / cm 2 、4.9mAh / cm 2 、5mAh / cm 2 The compaction density of the negative electrode is 1.4 g / cm 3 -1.9g / cm 3 For example, the compaction density of the negative electrode can be 1.4 g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 In a preferred embodiment, the surface capacity of the negative electrode is 2 mAh / cm 2 -4 mAh / cm 2 The compaction density of the negative electrode is 1.5 g / cm3 -1.8g / cm 3 The surface capacity of the negative electrode refers to the amount of electricity that can be stored per unit area of the negative electrode material, usually expressed in mAh / cm 2 The unit is expressed; if the surface capacity and compaction density of the negative electrode are too low, the energy density of the battery will be too low, while if the surface capacity and compaction density of the negative electrode are too high, the dynamic performance of the electrolyte will be difficult to meet the high and low temperature requirements. Therefore, the present invention can ensure that the battery has a high energy density while maintaining excellent overall dynamic performance of the battery, thereby further improving the low-temperature fast charging and low-temperature discharging performance of the battery.
[0037] Further, according to the battery of the present invention, the ratio of the unit area capacity of the negative electrode to the positive electrode is c; the mass content of the additive A a wt% and the ratio of the unit area capacity of the negative electrode to the positive electrode c satisfy the relationship: a≤70-(c-1.01)×1000. It should be noted that the ratio of the unit area capacity of the negative electrode to the positive electrode, that is, the N / P ratio, is represented by c in the present invention, which is usually used to measure the matching degree of the capacity of the negative electrode and the positive electrode materials; a lower ratio c can make the voltage of the positive electrode relatively low when the battery is fully charged, but too low a c value will greatly increase the probability of lithium precipitation when the battery is fully charged, and the cycle performance will be significantly deteriorated; therefore, the ratio c should be controlled within an appropriate range; at the same time, since the higher the c, the higher the positive electrode voltage will be when fully charged, the additive A fluoromononitrile compound will be difficult to withstand excessively high voltage, so its addition amount needs to be reduced accordingly, thereby improving the high temperature cycle performance of the battery when fully charged.
[0038] According to the battery of the present invention, in a specific embodiment, the ratio c of the unit area capacity of the negative electrode to the positive electrode is 1.08≥c≥1.01. Exemplarily, the ratio c of the unit area capacity of the negative electrode to the positive electrode can be 1.08, 1.07, 1.06, 1.05, 1.04, 1.03, 1.02, or 1.01.
[0039] According to the battery of the present invention, the compaction density of the positive electrode is 3g / cm 3 -4.5g / cm 3 For example, the compaction density of the positive electrode may be 3 g / cm 3 、3.1g / cm 3 、3.2g / cm 3 、3.3g / cm 3 、3.4g / cm 3 , 3.5g / cm 3 、3.6g / cm 3 、3.7g / cm 3 、3.8g / cm 3 、3.9g / cm3 , 4g / cm 3 , 4.1g / cm 3 , 4.2g / cm 3 , 4.3g / cm 3 4.4g / cm 3 , 4.5g / cm 3 .
[0040] The negative electrode and the negative electrode active material thereof in the present invention can be prepared according to methods known in the art or obtained through commercial channels.
[0041] According to the lithium ion battery of the present invention, the lithium ion battery further comprises a separator, and the separator may also be a separator conventionally used in the art, such as a PP film, a PE film, and the like.
[0042] The lithium-ion battery of the invention can be prepared by conventional methods in the art. Specifically, the positive electrode, the isolation membrane and the negative electrode can be stacked in sequence, and then the battery cell can be obtained through the processes of baking, liquid injection, formation, packaging, etc.
[0043] The present invention will be described in further detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0044] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.
[0045] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] Example 1
[0047] The lithium ion battery of the present invention is obtained by the following method:
[0048] 1) Preparation of positive electrode
[0049] The positive electrode active materials lithium cobalt oxide (LiCoO2), polyvinylidene fluoride (PVDF), SP (super P) and carbon nanotubes (CNT) are mixed in a mass ratio of 96:2:1.5:0.5, and N-methylpyrrolidone (NMP) is added and stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode active slurry with uniform fluidity; the positive electrode active slurry is evenly coated on both surfaces of the aluminum foil; the coated aluminum foil is dried, and then rolled and cut to obtain the desired positive electrode sheet, and the compaction density of the positive electrode sheet is 3.75g / cm 3 The surface capacity of the positive electrode is 2.86 mAh / cm 2 .
[0050] 2) Negative electrode preparation
[0051] The negative electrode active materials artificial graphite, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, conductive carbon black (SP) and single-walled carbon nanotubes (SWCNTs) were mixed in a mass ratio of 94.5:2.5:1.5:1:0.5, and deionized water was added to obtain a negative electrode active slurry under the action of a vacuum mixer; the negative electrode active slurry was evenly coated on both surfaces of the copper foil; the coated copper foil was dried at room temperature, then transferred to an oven at 80°C for drying for 10 hours, and then cold pressed and cut to obtain a negative electrode sheet, the compaction density of the negative electrode sheet was 1.6 g / cm 3 The surface capacity of the negative electrode is 3 mAh / cm 2 .
[0052] 3) Preparation of electrolyte
[0053] In a glove box filled with argon (H2O<0.1ppm, O2<0.1ppm), the solvent was mixed evenly according to the mass ratio of PC / EC / DEC / FEC (additive B) / fluoropropionitrile (additive A) of 10:5:65:10:10; then 12wt% of LiPF6 and 1wt% of LiTFSI (a total of 13wt% of lithium salt added) based on the total mass of the electrolyte were quickly added thereto, followed by 3wt% of PS, 1wt% of LiDFOB, 2wt% of HTCN and 1wt% of ADN based on the total mass of the electrolyte, and after stirring evenly, the desired electrolyte was obtained after passing the moisture and free acid tests; the mass concentration of cobalt element in the electrolyte is as described in Table 1.
[0054] 4) Preparation of lithium-ion batteries
[0055] The positive electrode sheet of step 1), the negative electrode sheet of step 2) and the separator are stacked in the order of positive electrode sheet, separator and negative electrode sheet, and then wound to obtain a battery cell; the battery cell is placed in an outer packaging aluminum foil, and the electrolyte of step 3) is injected into the outer packaging, and after vacuum packaging, standing, forming, shaping, sorting and other processes, the separator redundancy is controlled to W, and the specific amount is as described in Table 1 to obtain a lithium ion battery. The battery of the present invention has a charge and discharge range of 3.0-4.45V.
[0056] Example 2 Group
[0057] Example 2 was carried out with reference to Example 1, except that the mass contents of additive A and additive B were changed, as shown in Tables 1 and 2 for details.
[0058] Example 3 Group
[0059] Example 3 was carried out with reference to Example 1, except that the mass content d of lithium bis(trifluoromethylsulfonyl)imide and / or lithium bis(fluorosulfonyl)imide was changed, see Table 1 and Table 2 for details.
[0060] Example 4 Group
[0061] The fourth embodiment group was carried out in accordance with the first embodiment, except that the surface capacity ratio c of the positive and negative electrodes was changed, as shown below. For other parameters, see Table 1 and Table 2:
[0062] In Example 4-1, the surface capacity ratio c of the positive and negative electrodes is 1.01, and the surface capacity of the negative electrode is 2.89 mAh / cm 2 ;
[0063] In Example 4-2, the surface capacity ratio c of the positive and negative electrodes is 1.08, and the surface capacity of the negative electrode is 3.09 mAh / cm 2 ;
[0064] In Example 4-3, the surface capacity ratio c of the positive and negative electrodes is 1.1, and the surface capacity of the negative electrode is 3.15 mAh / cm 2 .
[0065] Comparative Example 1
[0066] Comparative Example 1 was carried out with reference to Example 1, except that additive A was not added to the electrolyte, see Table 1 and Table 2 for details.
[0067] Comparative Example 2
[0068] Comparative Example 2 was carried out with reference to Example 1, except that additive B was not added to the electrolyte, as shown in Tables 1 and 2 for details.
[0069] Comparative Example 3
[0070] Comparative Example 3 was carried out with reference to Example 1, except that the content of the linear ester solvent in the electrolyte was less than 30 wt %, see Table 1 and Table 2 for details.
[0071] Comparative Example 4
[0072] Comparative Example 4 was carried out with reference to Example 1, except that the mass content of ethylene carbonate in the cyclic ester solvent in the electrolyte was greater than 10 wt %, see Table 1 and Table 2 for details.
[0073] Table 1
[0074]
[0075] Table 2
[0076]
[0077] Test Case
[0078] The performance tests were performed on the lithium-ion batteries obtained in the examples and comparative examples, and the test results are shown in Tables 2 and 3.
[0079] 1) Low temperature 0℃ discharge test
[0080] The battery in Table 1 was fully charged at a rate of 1C within the charge and discharge cut-off voltage range at 25°C, and then the battery was discharged at a rate of 1C within the charge and discharge cut-off voltage range at 25°C, and the discharge capacity was recorded as C1; the battery was then fully charged at a rate of 1C within the charge and discharge cut-off voltage range at 25°C, and then the battery was discharged at a rate of 1C within the charge and discharge cut-off voltage range at 0°C, and the discharge capacity was recorded as C2. The low-temperature discharge capacity retention rate R0=C2 / C1 was calculated. The results are shown in Table 3.
[0081] 2) Low temperature 0℃ cycle performance test
[0082] The battery in Table 1 was charged and discharged in a 2C discharge range at 0°C. The discharge capacity of the first week of the test was calculated as x1mAh, and the discharge capacity of the Nth cycle was calculated as y1mAh. The capacity of the Nth week was divided by the capacity of the first week to obtain the cycle capacity retention rate R1=y1 / x1 of the Nth week. The number of cycles of the battery when the cycle capacity retention rate R1 is 80% was recorded. The results are shown in Table 3.
[0083] 3) High temperature 45℃ cycle performance test
[0084] The battery in Table 1 was charged and discharged in a 2C discharge range at 45°C within the charge and discharge cut-off voltage range. The discharge capacity of the first week of the test was calculated as x2 mAh, and the discharge capacity of the Nth cycle was calculated as y2 mAh. The capacity of the Nth week was divided by the capacity of the first week to obtain the cycle capacity retention rate R2=y2 / x2 of the Nth week. The number of cycles of the battery when the cycle capacity retention rate R2 was 80% was recorded. The results are shown in Table 3.
[0085] Table 3
[0086]
[0087]
[0088] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. An electrolyte, characterized in that: It comprises additive A, additive B, linear ester solvent and cyclic ester solvent; the additive A comprises fluoromononitrile compound, and the additive B comprises fluoroethylene carbonate; Based on the total mass of the electrolyte, the mass content of the additive A is awt%, the mass content of the additive B is b wt%, and the electrolyte satisfies the relationship: b≥a / 5; Based on the total mass of the electrolyte, the mass content of the linear ester solvent is ≥30wt%, and the mass content of the ethylene carbonate contained in the cyclic ester solvent is ≤10wt%.
2. The electrolyte according to claim 1, characterized in that The electrolyte satisfies at least one of the conditions (i) to (ii): (i) 2 wt%≤a wt%≤50 wt%, preferably, 3 wt%≤a wt%≤15 wt%; (ii) 1 wt%≤b wt%≤20 wt%, preferably, 5 wt%≤b wt%≤15 wt%.
3. The electrolyte according to claim 1, characterized in that The fluoromononitrile compound includes at least one of fluoropropionitrile, 3,3-difluoropropionitrile, 2-fluoroisobutyronitrile, fluoroacetonitrile and derivatives thereof; and / or, the linear ester solvent comprises at least one of propyl propionate, ethyl propionate, ethyl butyrate, diethyl carbonate, ethyl methyl carbonate and derivatives thereof; And / or, the cyclic ester solvent includes at least one of ethylene carbonate, propylene carbonate and vinylene carbonate.
4. The electrolyte according to claim 1, characterized in that The electrolyte further comprises a lithium salt, a sulfur-containing additive, a boron-containing additive and a nitrile compound; Preferably, the lithium salt includes at least one of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide; Preferably, the sulfur-containing additive includes at least one of 1,3-propane sultone, 1-propylene-1,3-sultone, 5-methyloxathiolane 2,2-dioxide, 1,3-propylene sultone, 2,4-butane sultone and 1,4-butane sultone; Preferably, the boron-containing additive includes at least one of lithium tetrafluoroborate, lithium difluorooxalatoborate, and lithium dioxalatoborate; Preferably, the nitrile compound includes one or more of 1,3,5-hexanetrinitrile, adiponitrile, succinonitrile, ethylene glycol bis(propionitrile) ether and tris(3-cyanopropyl)phosphate.
5. The electrolyte according to claim 4, characterized in that The lithium salt includes lithium bis(trifluoromethylsulfonyl)imide and / or lithium bis(fluorosulfonyl)imide, and the mass content of the lithium bis(trifluoromethylsulfonyl)imide and / or lithium bis(fluorosulfonyl)imide is d wt% based on the total mass of the electrolyte; The electrolyte also satisfies the relationship: d≤2a; preferably, 0wt%≤dwt%≤20wt%.
6. A lithium ion battery, characterized in that: The electrolyte, the positive electrode and the negative electrode according to any one of claims 1 to 5; The positive electrode comprises lithium cobalt oxide; Based on the total mass of the electrolyte, the mass concentration of cobalt element in the electrolyte is e ppm; The mass content a wt % of the additive A and the mass concentration e ppm of the cobalt element in the electrolyte satisfy the relationship: a≥e / 500; preferably, e≤10000 ppm.
7. The lithium-ion battery according to claim 6, characterized in that: The surface capacity of the negative electrode is 2 mAh / cm 2 -5mAh / cm 2 The compaction density of the negative electrode is 1.4 g / cm 3 -1.9g / cm 3 ; Preferably, the surface capacity of the negative electrode is 2 mAh / cm 2 -4 mAh / cm 2 The compaction density of the negative electrode is 1.5 g / cm 3 -1.8g / cm 3 .
8. The lithium-ion battery according to claim 6, characterized in that The ratio of the unit area capacity of the negative electrode to the positive electrode is c; The ratio of the mass content a wt % of the additive A to the unit area capacity of the negative electrode and the positive electrode c satisfies the relationship: a≤70-(c-1.01)×1000.
9. The lithium-ion battery according to claim 8, characterized in that: A ratio c of the unit area capacity of the negative electrode to the positive electrode satisfies 1.08≥c≥1.
01.
10. The lithium ion battery according to claim 6, characterized in that: The compaction density of the positive electrode is 3g / cm 3 -4.5g / cm 3 .
Citation Information
Patent Citations
Preparation method of high-safety high-voltage electrolyte containing nitrile compounds
CN114400379A
High-voltage electrolyte suitable for fast-charging lithium battery and lithium battery
CN116799300A
Lithium metal secondary battery electrolyte and application thereof
CN117976980A
Quick-charge type lithium ion battery and preparation method and application thereof
CN118553914A
Nonaqueous electrolyte secondary battery
JP2007207723A
Cited By
Secondary battery and electronic device
WO2026149372A1
